Application of the triple helix model in the revitalisation of cities: the case of Brazil. (2019) - Pique, Josep Miquel; Miralles, Francesc; Teixeira, Clarissa Stefani; Gaspar, Jadhi Vincki; Filho, José Roberto Branco Ramos
A new trend in urban projects has risen around a common problem: old urban spaces are losing most of their productive capabilities and becoming obsolete. In most cases, these spaces are revitalised by transforming them in knowledge based development areas. The aim of this paper is to understand how these transformation projects are developed. After reviewing the theoretical framework of the triple helix model and knowledge based urban development, using a multiple case approach, we analyse four Brazilian cities that are in the process of urban revitalization: Porto Digital in the city of Recife; Porto Maravilha in Rio de Janeiro; 4° Distrito in Porto Alegre; and Centro Sapiens in Florianópolis. The 22@Barcelona project, a world reference of brownfield transformations, is used as a control case. The findings shed light on how universities, government and industry, with the society and environment contribute to the urban, economic, social and governance transformation.